2007
DOI: 10.1007/s11255-007-9214-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of extracorporeal shock wave lithotripsy outcomes for proximal and distal ureteric stones

Abstract: ESWL outcomes for the ureteral calculi support the use of lithotripsy particularly for stones <100 mm(2). Treatment efficacy was not significantly different among stones localized in proximal and distal ureters. Degree of obstruction did not affect the ESWL outcomes in the proximal ureter, but it adversely affected SFR in the distal ureter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Because of its noninvasive and practical nature, SWL has been the preferred therapeutic option [6][7][8], but its success depends on the location of the treated stone(s), with greater success in the management of proximal ureteral calculi. The success rates tend to decrease for distal stones, while stones treated in an emergency setting have a high success rate, similar to those treated with delayed lithotripsy [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its noninvasive and practical nature, SWL has been the preferred therapeutic option [6][7][8], but its success depends on the location of the treated stone(s), with greater success in the management of proximal ureteral calculi. The success rates tend to decrease for distal stones, while stones treated in an emergency setting have a high success rate, similar to those treated with delayed lithotripsy [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The success rates tend to decrease for distal stones, while stones treated in an emergency setting have a high success rate, similar to those treated with delayed lithotripsy [6][7][8][9][10][11][12]. However, the clinical introduction of URS has significantly changed the treatment concepts for ureteral stones.…”
Section: Introductionmentioning
confidence: 99%
“…Conflicting data are presented in a review comparing stone-free rates of 44 proximal and 24 distal ureteral stones. With a similar mean number of shocks delivered, the proximal stones were treated successfully in 86.3% of cases, not significantly different from the 79.1% stone-free rate in cases of distal stones (P = 0.17) [77]. Stone fragility, as determined by the acoustic and mechanical properties corresponding to the chemical composition of the stone, directly influences the success of SWL.…”
Section: Extracorporeal Shock Wave Lithotripsymentioning
confidence: 86%
“…Many studies showed that the likelihood of SWL treatment failure increases with more severe obstruction [12,13]. It was reported that in patients with proximal and distal ureteral stone the SWL outcome was affected by hydronephrotic grade [14,15]. In contrast to these reports, some authors concluded that urinary obstruction does not affect the success in terms of stone clearance with SWL [16,17].…”
Section: Discussionmentioning
confidence: 99%